Clinical Utility of Chest Computed Tomography in Patients with Rib Fractures CT Chest and Rib Fractures - Chapman, Brandon C. (Arch Trauma Res, 2016)
BACKGROUND: Chest CT is more sensitive than a chest X-ray (CXR) in diagnosing rib fractures; however, the clinical significance of these fractures remains unclear. OBJECTIVES: The purpose of this study was to determine the added diagnostic use of chest CT performed after CXR in patients with either known or suspected rib fractures secondary to blunt trauma. METHODS: Retrospective cohort study of blunt trauma patients with rib fractures at a level I trauma center that had both a CXR and a CT chest. The CT finding of ≥ 3 additional fractures in patients with ≤ 3 rib fractures on CXR was considered clinically meaningful. Student’s t-test and chi-square analysis were used for comparison. RESULTS: We identified 499 patients with rib fractures: 93 (18.6%) had CXR only, 7 (1.4%) had chest CT only, and 399 (79.9%) had both CXR and chest CT. Among these 399 patients, a total of 1,969 rib fractures were identified: 1,467 (74.5%) were missed by CXR. The median number of additional fractures identified by CT was 3 (range, 4 - 15). Of 212 (53.1%) patients with a clinically meaningful increase in the number of fractures, 68 patients underwent one or more clinical interventions: 36 SICU admissions, 20 pain catheter placements, 23 epidural placements, and 3 SSRF. Additionally, 70 patients had a chest tube placed for retained hemothorax or occult pneumothorax. Overall, 138 patients (34.5%) had a change in clinical management based upon CT chest. CONCLUSIONS: The chest X-ray missed ~75% of rib fractures seen on chest CT. Although patients with a clinical meaningful increase in the number of rib fractures were more likely to be admitted to the intensive care unit, there was no associated improvement in pulmonary outcomes.